2005
DOI: 10.1103/physrevb.72.035333
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the atomistic mechanics of single crystalline silicon wires of nanometer width

Abstract: Tensile deformation behavior of silicon ͑Si͒ wires with nanometer widths, synthesized by nanometer-tip contact and successive retraction, was studied by atomistic combined microscopy of high-resolution transmission electron microscopy/scanning probe microscopy. The elastic limit, Young's modulus, and strength of individual Si nanowires were investigated based on the mechanics of materials at an atomic scale. It was found that both Young's modulus and strength increased to 18± 2 and 5.0± 0.3 GPa, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
117
0
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(141 citation statements)
references
References 65 publications
12
117
0
12
Order By: Relevance
“…A more in-depth stress study in [8] reveals that the uniaxial tensile stress/strain level for similar 2.0 lm long GAA Si nanowires can be up to 5.6 GPa/3.3% considering both in-plane and out-ofplane buckling using both top and tilted-view SEM micrographs. According to [9] and as expected from the buckling profile in the SEM micrograph in Fig. 3, such strained Si nanowires are in the elastic regime and therefore, no carrier degradation is expected due to no plastic deformation in the channel.…”
Section: Introductionsupporting
confidence: 60%
“…A more in-depth stress study in [8] reveals that the uniaxial tensile stress/strain level for similar 2.0 lm long GAA Si nanowires can be up to 5.6 GPa/3.3% considering both in-plane and out-ofplane buckling using both top and tilted-view SEM micrographs. According to [9] and as expected from the buckling profile in the SEM micrograph in Fig. 3, such strained Si nanowires are in the elastic regime and therefore, no carrier degradation is expected due to no plastic deformation in the channel.…”
Section: Introductionsupporting
confidence: 60%
“…24. While these predictions have been observed in some experiments [67,[300][301][302][303], other experiments have found that regardless of boundary condition, the elastic properties of silicon nanowire-based NEMS show little difference from the elastic properties of the bulk materials [227,304,305].…”
Section: Surface Cauchy-born Model: Nanowire Resonatormentioning
confidence: 87%
“…High-resolution transmission electron microscopy ͑HRTEM͒ enables us to observe the atomic configuration directly. [40][41][42][43][44][45][46][47][48][49][50] However, the electrical and mechanical properties of Pt ASWs have not been related directly to the atomic configuration observed by HRTEM.…”
Section: Introductionmentioning
confidence: 99%